Genome-wide association mapping of seed oligosaccharides in chickpea - Elango, Dinakaran; Wang, Wanyan; Thudi, Mahender; Sebastiar, Sheelamary; Ramadoss, Bharathi Raja; Varshney, Rajeev K. (Frontiers in Plant Science, 2022)
Chickpea (Cicer arietinum L.) is one of the major pulse crops, rich in protein, and widely consumed all over the world. Most legumes, including chickpeas, possess noticeable amounts of raffinose family oligosaccharides (RFOs) in their seeds. RFOs are seed oligosaccharides abundant in nature, which are non-digestible by humans and animals and cause flatulence and severe abdominal discomforts. So, this study aims to identify genetic factors associated with seed oligosaccharides in chickpea using the mini-core panel. We have quantified the RFOs (raffinose and stachyose), ciceritol, and sucrose contents in chickpea using high-performance liquid chromatography. A wide range of variations for the seed oligosaccharides was observed between the accessions: 0.16 to 15.13 mg g-1 raffinose, 2.77 to 59.43 mg g-1 stachyose, 4.36 to 90.65 mg g-1 ciceritol, and 3.57 to 54.12 mg g-1 for sucrose. Kabuli types showed desirable sugar profiles with high sucrose, whereas desi types had high concentrations RFOs. In total, 48 single nucleotide polymorphisms (SNPs) were identified for all the targeted sugar types, and nine genes (Ca_06204, Ca_04353, and Ca_20828: Phosphatidylinositol N-acetylglucosaminyltransferase; Ca_17399 and Ca_22050: Remorin proteins; Ca_11152: Protein-serine/threonine phosphatase; Ca_10185, Ca_14209, and Ca_27229: UDP-glucose dehydrogenase) were identified as potential candidate genes for sugar metabolism and transport in chickpea. The accessions with low RFOs and high sucrose contents may be utilized in breeding specialty chickpeas. The identified candidate genes could be exploited in marker-assisted breeding, genomic selection, and genetic engineering to improve the sugar profiles in legumes and other crop species.